Coffee Shop As a Media for Self-Actualization Today's Youth - Salendra, Salendra (Jurnal The Messenger, 2014)
Trends go to a coffee shop that is currently self-actualization can be a medium for today's youth. In this study, the author uses Dramaturgy Theory introduced by Erving Goffman 1955 in The Presentation of Self in Everyday Life.                             This research methods using qualitative methodology and data collection technique was done by observation, interviews and   study by literature. Trends goes to coffee shop by teen nowdays be assumed as teen s activity to follow modern life style and it does to complete needs of self actualization.                       It was concluded that the phenomenon of teenage habit to go to the coffee shop is an adolescent self-actualization behaviors performed by following a growing trend. Dramaturgy Theory discusses the two sides of teenage life in self actualize, front stage of a teenager is a person who has wide connections and likes to follow the trend of going to the coffee shop, and the back stage of the teenager is the pupil / student in an educational institution and a child in a family whose primary job is to learn and serve the elderly.